DIFFERENT CONJUNCTIVAL AUTOGRAFT TECHNIQUES FOR PTERYGIUM SURGICAL EXCISION, A CASE SERIES: Poster Presentation - Case Series - Resident - ANNISAK FITRIYANA; Angga Fajriansyah; Arief Akhdestira Mustaram; Patriotika Muslima; Elfa Ali Idrus (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Pterygium is a wing shaped fibrovascular growth that extends from the conjunctiva onto the cornea. There are many techniques available for pterygium removal, from simple excision to excision and repair of the defect with modified techniques. Case Illustration : 1. A 50-year-old woman presented with a grade II pterygium in both of her eyes. She was undergone sliding flap pterygium excision for her right eye. Case 2. A 32-year-old man presented with a grade II pterygium in his left eye. He was then undergone rotational flap pterygium excision for his left eye. Case 3 A-55-year-old woman presented with a grade II-III double head pterygium. She was later undergone modified conjunctival autograft double head pterygium excision for his left eye. Discussion : Surgical management is the gold standard for pterygium treatment. Indications for pterygium excision include decreased visual acuity due to astigmatism, obstruction of visual axis, repeated irritation and cosmetics. Surgical techniques for excision of the pterygium include bare sclera excision, tissue grafting using conjunctival graft, membrane transplantation amnion and limbal- conjunctival autograft. There are several choices of conjunctival graft techniques after pterygium excision, such as conjunctival sliding flap, conjunctival rotational flap, and modified conjunctival autograft. Modified conjunctival autograft technique was performed for double head pterygium management. The technique consisting of horizontally modified conjunctival autograft and vertically modified conjunctival autograft. Conclusion : The choices of surgical excision techniques for pterygium depends on the grades of the pterygium and operator’s preference.